ANALISIS PENGARUH PROMOSI DAN ATMOSFER GERAI TERHADAP IMPULSE BUYING MELALUI EMOSI POSITIF SEBAGAI VARIABEL INTERVENING - Fahd, Faishal; Sugiarto, Yohanes (Faculty of Economics and Business Diponegoro University, 2015)
This research aims to understand the extent to which the promotion of fashion store outletsin the atmosphere and moseim woman ( positive emotion ) affecting the mood of consumers in doing the decision of the purchase .As we know , the workaholic expenditure shopaholic (Person that like shopping too much ) very happy to support the activities of the atmosphere or room of their shopping .For it , the promotion of being attractive and comfortable atmosphere outlets need to be made to win an industrial competition in this field .This study using quantitative methods .Data collected by engineering the questionnaire .Of respondents to this research is woman who was shopping with the number of respondents as many as 100 people .Quantitative methods include validity and reliability , test the assumption of the classics , testing the hypothesis through the f , t and test the coefficients determined ( r2 ) Engineering analysis of data used is linear regression analysis.And this research is used to test for detecting sobel intervening variable is a positive emotion.This research result indicates that promotion and store athmosphere, positive atmosphere and influence significantly to a positive emotion, the positive emotion accepted as variable intervening in a mediate promotion and the other on impulse buying.